Alterations of Resting-State Locus Coeruleus Functional Connectivity After Transdermal Trigeminal Electrical Neuromodulation in Insomnia - Um, Yoo Hyun; Wang, Sheng-Min; Kang, Dong Woo; Kim, Nak-Young; Lim, Hyun Kook (Frontiers in Psychiatry, 2022)
Background: Transdermal trigeminal electrical neuromodulation(TTEN) is a novel treatment modality that is known for noradrenergic modulation through trigeminal nerve and locus coeruleus. This study aimed to demonstrate the alterations of locus coeruleus(LC) functional connectivity(FC) in insomnia patients after a 4-week TTEN. Methods: The Cefaly device targeting the ophthalmic division of the trigeminal nerve was applied to a total of 12 insomnia patients to monitor for the effects of TTEN. All the patients went through a 4-week daily 20 minute TTEN sessions before bedtime. Baseline and post-TTEN demographic data, polysomnography (PSG) parameters and insomnia severity index (ISI) were attained. Pre- and post-intervention resting-state functional magnetic resonance imaging data were collected. LC FC differences were measured between the pre-and post-TTEN groups through seed-to-voxel analysis. Correlation analyses were conducted between LC FC changes after TTEN, ISI score changes and PSG parameter changes. Results: There was a significantly decreased LC FC with occipital and temporal cortices after a 4-week of TTEN. However, there was no significant correlation between LC FC, ISI score changes and PSG parameter changes. Conclusion: TTEN can be a promising intervention that can modulate LC FC in insomnia patients, by targeting hyperarousal symptoms of insomnia. [The data presented in the study are from a study exploring the effect of TTEN on insomnia(www.clinicaltrials.gov NCT04838067)]